Hatched! - Yap, She Fong. (2011)
Hatched! is the thesis short film completed as a culmination of my four years of tertiary education at the School of Art, Design and Media. Developed as a project exploring the combination of 2D and stop-motion animation, the film tells the dark adventures of a newborn chick as it takes its first steps into our world. Initially a film called “Tomato… …Juiced”, Hatched! had undergone concept, story and design changes to result in the film that it is today. Most importantly however, is the fact that the project has stayed true to its fundamental concept of using different animation techniques as visually aesthetic storytelling devices. This FYP report will cover the evolution of Hatched! from Tomato… …Juiced, by documenting in detail the process of conceptualising, producing, and finishing this short film. In addition, it will provide an insight into the challenges faced, and the lessons learnt from the experience of this project.